2020
DOI: 10.3389/fendo.2020.00469
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Live Birth Rate in Patients With Thin Endometrium: A Real-World Single-Center Experience

Abstract: Background: Studies have shown that patients with a thin endometrial thickness (EMT < 7 or 8 mm) during IVF/ICSI tend to have adverse pregnancy outcomes, and this has caused much anxiety to both patients and physicians when confronted with a thin EMT. Method: From January 2015 to December 2018, patients with a thin EMT < 7 mm on the day of hCG administration during their first GnRH agonist IVF/ICSI cycle were included. According to the hysteroscopy results, patients were classified into totally normal (Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, in those combined with thin endometrium, the clinical pregnancy rate was 25.62%, live birth rate was 13.30%, and early miscarriage rate was 36.54%. Our results were in line with the previous studies [4,20].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, in those combined with thin endometrium, the clinical pregnancy rate was 25.62%, live birth rate was 13.30%, and early miscarriage rate was 36.54%. Our results were in line with the previous studies [4,20].…”
Section: Discussionsupporting
confidence: 94%
“…IUAs combined with thin endometrium (< 7 or 8 mm) has been demonstrated to signi cantly decrease implantation and pregnancy rate [4,33]. Guo Z and coworkers suggested that for women with a thin endometrium and were undergoing IVF, FET was associated with signi cantly higher incidences of live birth, clinical pregnancy, and biochemical pregnancy than in the fresh ET group [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terms in articles using gender-inclusive language included patients, [14][15][16][17] parents, 18,19 and pregnant teens. 18 The field of first authors was associated with the use of inclusive language ( 2 (19) = 84.83, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…However, whether the surgical removal of all uterine pathologies (i.e., subcentimeter polyps or filmy intrauterine adhesions) improves IVF and embryo transfer outcomes remains controversial (60). The role of surgical interventions for refractory endometrium adds another complex layer, given that often, a thin endometrium results from a previous intrauterine operation and that the rate of intrauterine adhesion reformation is high (61,62). The most practical approach is via the reservation of operative hysteroscopy in patients who fail to achieve adequate EMT despite attempts using various endometrial preparation protocols (as previously described) to rule out previously undetected intrauterine adhesions or in those with an abnormal transvaginal ultrasound result concerning for uterine pathology.…”
Section: Surgical Interventions To Optimize Emtmentioning
confidence: 99%